Probing the Amyloid Peptide-Membrane Interaction Using a Liposome Model System - Tao, Liguo; Cao, Yunpeng; Ma, Cuixia; Wang, J.; Lin, L.; Liu, L.; Dong, Mingdong (Journal of Self Assembly and Molecular Electronics, 2023)
The aggregation of amyloid peptides is closely related to the pathogenesis of degenerative diseases. More and more evidence implies that the proto fibrillar intermediates rather than the mature amyloid fibrils are the toxic species related to the membrane disruption. In this work we found that the self-assembling intermediates of Aβ33-42 during early aggregation are able to break down the liposome. During the process of amyloid peptide (Aβ33-42) intermediate binding to liposome, the β-sheet secondary structure of peptide took change on the molecular level which was characterized by circular dichroism (CD) spectra. The small micelles were formed due to the disruption of amyloid peptide, and further to grow into big irregular complexes with further incubation, which is characterized by the assay of disrupting liposome membrane and atomic force microscopy (AFM). This founding paved the way to understand the interactions between the amyloid peptide and membranes, and support the amyloid peptide nanostructure formed in the early stage of aggregation has good affinity with membrane.